2017
DOI: 10.1111/jgs.15058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of New Oral Anticoagulants on Prescribing Practices for Atrial Fibrillation in Older Adults

Abstract: BACKGROUND Warfarin is effective in preventing stroke and systemic embolism in atrial fibrillation (AF) but has several limitations. The new oral anticoagulants (NOACs) address many of these limitations but their impact on prescribing practices in older adults with AF is unknown. DESIGN Retrospective observational cohort study SETTING Academic medical center in St. Louis, MO, USA PARTICIPANTS Patients age ≥75 with AF admitted from October 2010 through September 2015 (N=6568, 50% female, 15% non-white). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 22 publications
2
21
1
1
Order By: Relevance
“…The increase in oral anticoagulant therapy in our study was mainly due to an increase in the NOAC prescription (from 11.8 to 33.3%; p < 0.001). The prescription of NOACs has increased, and use of VKAs has dropped significantly in many countries [21][22][23], and a progressive increase in the proportion of patients newly diagnosed with AF receiving guideline-recommended therapy, potentially driven by the availability of NOACs, was also observed [24][25][26][27]. But in the period that was covered by our study (and it is also the case now) all NOACs in Poland were [28].…”
Section: Discussionsupporting
confidence: 52%
“…The increase in oral anticoagulant therapy in our study was mainly due to an increase in the NOAC prescription (from 11.8 to 33.3%; p < 0.001). The prescription of NOACs has increased, and use of VKAs has dropped significantly in many countries [21][22][23], and a progressive increase in the proportion of patients newly diagnosed with AF receiving guideline-recommended therapy, potentially driven by the availability of NOACs, was also observed [24][25][26][27]. But in the period that was covered by our study (and it is also the case now) all NOACs in Poland were [28].…”
Section: Discussionsupporting
confidence: 52%
“…28,33,47 It reflects that clinicians are aware of NOACs and had a better understanding of indications for their use along with their use on antiplatelet therapy. 31,32 In contrast, antiplatelet use, paroxysmal AF, history of bleeding, history of falls, dementia, psychosis, liver disease, and use of antiplatelet were pointed as the potential reasons for OAC non-prescription by two of the studies. 29,35 Similarly, patients at higher risk of stroke who are at high risk of bleeding were found less likely to receive OAC.…”
Section: Discussionmentioning
confidence: 97%
“…This review describes the predictors of warfarin and NOAC utilization in patients with atrial fibrillation. From this review, it is revealed that NOACs were more likely to be prescribed in younger patients, [31][32][33][34]38 while warfarin was mostly used in older patients (≥75 years), except in patients ≥85 years. 27,30,32,36 In older patients, extra precautions should be followed while administering the drug, and they might have a higher incidence of contraindications with increasing age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations